Development and evaluation of mandarin language exploration game for non-native speakers / Aznoora Osman and Siti Nabilah Abdul Malek - Osman, Aznoora; Abdul Malek, Siti Nabilah (UiTM Cawangan Perlis, 2017)
This paper discusses the development and evaluation of an exploration game for Mandarin language. The game focuses on mastering basic vocabularies in Mandarin for non-native speakers. Emphasis is given on word recall and pronunciation of Chinese characters. The evaluation consisted of testing session with students to discover the effects of the game towards the students’ confidence in word recall and pronunciation of Chinese characters. The target audience of the project is students in UiTMPerlis Branch, who undertake Level 1 Mandarin language course. The research methodology that was used in this project is spiral model. There are four phases in the spiral model which are game idea specification, game design prototype, playtesting and evaluation. Game interface was designed by using Unity 3D software. The exploration game was constructed by integrating two elements from Octalysis’ game framework into the exploration game which are ownership and avoidance. Ownership is the element where players are inspired to complete the game when they have sense of owning something. Avoidance element is based on the avoidance of negative circumstances. Testing phase employs user testing which was conducted with 19 bachelor degree students from Level 1 Mandarin language class. From the results, it was discovered that generally, the exploration game has positively influenced the students’ confidence to recall and to pronounce Chinese characters. This could signify that exploration game is a promising tool in elevating confidence among language learners.